Legal Protection for Human Rights Defender in Indonesia - Siagian, Daniel Alexander; Muktiono; Prasetyo, Ngesti Dwi (The Islamic Education and Multiculturalism Foundation, 2024)
Legal protection of human rights defenders in Indonesia is crucial for the state to fulfil, promote and develop human rights. This research focuses on the reformulation of legal obscurity in regulations that have not legitimised the protection of human rights defenders. Various forms of vulnerability of human rights defenders in fact lead to human rights violations such as Criminalisation, Victimisation, Anti-SLAPP (Strategic Lawsuit Against Public Participation), Cyber Attacks and physical attacks intended for human rights defenders which reinforce Impunity. The facts show that the activities of human rights defenders are very vulnerable, it is appropriate to require legal protection in each of their activities. The vulnerability of the activities carried out by human rights defenders, which basically aims to contribute to the quality of State administration in promoting human rights, shows that protection for human rights defenders is important to be reformulated. By considering several important issues that are the focus of the research, the protection of Human Rights Defenders consists of, for instance, legal protection, which is not only related to the establishment of laws and regulations that guarantee the protection of Human Rights Defenders, but also to the elimination of laws that have the potential to threaten, restriction and violate Human Rights Defenders, guarantees and support for the activities of Human Rights Defenders, including the effectiveness of Human Rights Defenders in the process of advocacy, such as the right to information, communication with both government and non-government organisations, and recognition of Human Rights Defenders' advocacy. This also covers the guarantee of defenders' right to immunity for their advocacy activities.